Cost-effectiveness analysis of pembrolizumab monotherapy versus chemotherapy for previously untreated advanced non-small cell lung cancer. (1st September 2020) - Aziz, Mohamed Ismail Abdul; Tan, Ling Eng; Tan, Wan Hui Gloria; Toh, Chee-Keong; Loke, Lydia Pui Yee; Pearce, Fiona; Ng, Kwong
Abstract: Objective: To assess the cost-effectiveness of pembrolizumab monotherapy compared with standard chemotherapy for the treatment of advanced non-small cell lung cancer (NSCLC) in previously untreated adults who have a high programmed death ligand 1 (PD-L1) tumor proportion score of 50% or greater in Singapore. Materials and methods: A partitioned-survival analysis model was developed from a healthcare system's perspective that extrapolated clinical and economic outcomes of first-line pembrolizumab (maximum treatment duration of 2 years) versus platinum doublet chemotherapy over a 10-year time horizon for patients with advanced NSCLC. The model consisted of three health states: alive with no progression, alive with progression, and dead. Key clinical inputs were based on Kaplan-Meier survival curves from the interim (median follow-up = 11.2 months) and updated analysis (median follow-up = 25.2 months) of the KEYNOTE-024 randomized controlled trial. Local cost data were applied. Utilities were derived from published international estimates. Both one-way and multivariate probabilistic sensitivity analyses (PSA) were conducted to identify key drivers of the results. Results: Using the results from the updated analysis of KEYNOTE-024, patients treated with pembrolizumab experienced more quality adjusted life-years (QALYs), but incurred higher costs compared to chemotherapy over a 10-year time horizon (pembrolizumab: 1.9983 QALYs, SGD215, 761; chemotherapy: 1.1317 QALYs, SGD70, 444). The base-case incremental cost-effectiveness ratio (ICER) was SGD167, 692 per QALY gained. One-way sensitivity analysis showed the ICER was most sensitive to the cost of pembrolizumab, followed by the time horizon. Multivariate PSA indicated that pembrolizumab had 0% probability of being cost-effective at a hypothetical willingness-to-pay threshold of SGD100, 000 per QALY gained. Conclusion: While pembrolizumab is superior to standard chemotherapy in improving overall survival and progression-free survival, results suggest that it is unlikely to be cost-effective at its current price in Singapore. Factors including clinical effectiveness, safety, and budget impact should also be considered when making national funding decisions.